TANTANGAN DAN PELUANG JURUSAN TADRIS DI IAIN/STAIN - Mohammad Kosim (TADRIS: Jurnal Pendidikan Islam, 2009)
A consequence of dualism in education policy, the implementatin of tadris in IAIN often faces many problems. This paper will describe the history and the development of tadris in IAIN/STAIN. The discussion begins with the origin of tadris in IAIN, problems araise in the implementation of tadris in IAIN/STAIN, including the alumni’s problem. In addition, this article also reveals several opportunities for tadris graduation to develop madrasah as purely religious school to public islamic school as the result of the paradigm change.